The Potential of Anti-coronavirus Plant Secondary Metabolites in COVID-19 Drug Discovery as an Alternative to Repurposed Drugs: A Review - Alipour, Zahra; Zarezadeh, Somayeh; Ghotbi-Ravandi, Ali Akbar (Planta Medica, 2023)
In early 2020, a global pandemic was announced due to the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), known to cause COVID-19. Despite worldwide efforts, there are only limited options regarding antiviral drug treatments for COVID-19. Although vaccines are now available, issues such as declining efficacy against different SARS-CoV-2 variants and the aging of vaccine-induced immunity highlight the importance of finding more antiviral drugs as a second line of defense against the disease. Drug repurposing has been used to rapidly find COVID-19 therapeutic options. Due to the lack of clinical evidence for the therapeutic benefits and certain serious side effects of repurposed antivirals, the search for an antiviral drug against SARS-CoV-2 with fewer side effects continues. In recent years, numerous studies have included antiviral chemicals from a variety of plant species. A better knowledge of the possible antiviral natural products and their mechanism against SARS-CoV-2 will help to develop stronger and more targeted direct-acting antiviral agents. The aim of the present study was to compile the current data on potential plant metabolites that can be investigated in COVID-19 drug discovery and development. This review represents a collection of plant secondary metabolites and their mode of action against SARS-CoV and SARS-CoV-2.
Keywords: SARS-CoV-2; antivirals; phytochemicals; natural products; medicinal plants; alternative medicine